2016
DOI: 10.1021/acs.inorgchem.6b00352
|View full text |Cite
|
Sign up to set email alerts
|

Interconversion between [Fe4S4] and [Fe2S2] Clusters Bearing Amide Ligands

Abstract: Structural conversion of [Fe4S4] clusters into [Fe2S2] clusters has been suggested to be a fundamental process for some O2-sensing proteins. While the formation of [Fe2S2] clusters from synthetic [Fe4S4] clusters has been unprecedented, an all-ferric [Fe4S4](4+) cluster Fe4S4{N(SiMe3)2}4 (1) was found to split in the presence of pyridines, giving [Fe2S2] clusters Fe2S2{N(SiMe3)2}2(L)2 (2, L = pyridines). The structural conversion between [Fe4S4] and [Fe2S2] clusters appeared to be reversible, and the thermodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…These preliminary results and the aforementioned enzymatic studies suggested that [Fe 4 S 4 ] 3+ –alkyl clusters may be exceptionally reactive. Indeed, synthetic [Fe 4 S 4 ] 3+ clusters are generally more difficult to isolate than [Fe 4 S 4 ] 2+ clusters, and, to date, only a handful have been reported. Consequently, we sought a new strategy for isolating an [Fe 4 S 4 ] 3+ –alkyl cluster. We reasoned that incorporation of a noncoordinating anion into a tridentate ligand framework would allow for the generation of an [Fe 4 S 4 ] 3+ –alkyl cluster as a monocation instead of a dication, with the decreased molecular charge rendering the cluster less electrophilic.…”
Section: Introductionmentioning
confidence: 99%
“…These preliminary results and the aforementioned enzymatic studies suggested that [Fe 4 S 4 ] 3+ –alkyl clusters may be exceptionally reactive. Indeed, synthetic [Fe 4 S 4 ] 3+ clusters are generally more difficult to isolate than [Fe 4 S 4 ] 2+ clusters, and, to date, only a handful have been reported. Consequently, we sought a new strategy for isolating an [Fe 4 S 4 ] 3+ –alkyl cluster. We reasoned that incorporation of a noncoordinating anion into a tridentate ligand framework would allow for the generation of an [Fe 4 S 4 ] 3+ –alkyl cluster as a monocation instead of a dication, with the decreased molecular charge rendering the cluster less electrophilic.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular structures of 16 – 19 in the solid state were determined by single‐crystal X‐ray diffraction (Figures and ). The B−N distance in 17 (1.594(2) Å) is shorter than in the pyridine−B(C 6 F 5 ) 3 Lewis adduct (1.614(2) Å) and similar to that in the pyridine Lewis adduct 4 (1.584(2) Å), which is one of the shortest B−N bond lengths reported with a neutral boron Lewis acid.…”
Section: Methodsmentioning
confidence: 99%
“…Steric repulsions between the boratriptycene peri‐hydrogen atoms and the pyridine moiety caused its deviation by a tilt angle β of 15° from the triptycene central B⋅⋅⋅C axis (Figures c,d). The pyramidalization angle α in 17 (23.8°) is higher than in the Lewis adducts of pyridine with B(C 6 F 5 ) 3 (17.6°) or 1‐boraadamantane (20.0°) and comparable to that in the borabarrelene adduct 5 (24.5°) …”
Section: Methodsmentioning
confidence: 99%
“…Systematic work by Agapie has demonstrated electronic and catalytic modulation of iron cluster sites with interstitial light atoms [11, 12] . An incredibly thorough and long‐standing research program by Tatsumi has yielded highly complex iron‐sulfur structures of multiple nuclearities, [13–15] which include structures bearing an interstitial sulfide as found in the nitrogenase P‐cluster [16, 17] and a structure containing an interstitial oxide [18] . In a similar vein, the Holm group reported an iron‐sulfur cluster that incorporates a silyl‐nitride into the cluster core [19] .…”
Section: Figurementioning
confidence: 97%